Advertisement
Not a member of Pastebin yet?
Sign Up,
it unlocks many cool features!
- Base case:
- 1/(1 * 2) = 1/(1 + 1) ⇔ 1 = 1 ⇔ true
- Inductive hypothesis: 1/(1 * 2) + 1/(2 * 3) + ... + 1/(n * (n + 1)) = n/(n + 1) ⇒ 1/(1 * 2) + 1/(2 * 3) + ... + 1/(n * (n + 1)) + 1/((n + 1) * (n + 2)) = (n + 1)/(n + 2)
- ⇔ n/(n + 1) + 1/((n + 1) * (n + 2)) = (n + 1)/(n + 2)
- (n = -2 is outside the domain of our problem)
- ⇔ (n² + 2n)/(n + 1) + 1/(n + 1) = (n + 1)
- ⇔ (n² + 2n) + 1 = (n + 1)²
- ⇔ n² + 2n + 1 = n² + 2n + 1
- ⇔ 1 = 1
- ⇔ true
- ∴ 1/(1 * 2) + 1/(2 * 3) + ... + 1/(n * (n + 1)) = n/(n + 1) ∀n ≥ 1
Advertisement
Add Comment
Please, Sign In to add comment
Advertisement